Optimizing the Role of Primary Health Workers in the Implementation of Stunting Policies at the Village Level - Syaharuddin Syaharuddin; Suprapto Suprapto; Maria Kurni Menga; Yuriatson Yuriatson (Jurnal Pengabdian Masyarakat Edukasi Indonesia, 2026)
ntroduction: Stunting remains a persistent public health challenge in Indonesia, affecting child growth, cognitive development, and long-term productivity. Despite national policy efforts, gaps in implementation at the primary health care level continue to limit program effectiveness, particularly in community engagement and service utilization. This community service program aimed to strengthen the implementation of stunting prevention policies through a primary health care approach by enhancing the capacity of health workers and community health cadres, and improving household-level practices. Methods: A participatory approach was applied involving 50 participants, including health workers, cadres, and mothers of children under five. The program consisted of training sessions, nutrition education, mentoring of at-risk families, and routine growth monitoring over three months. Evaluation was conducted using pre- and post-test assessments, structured observations, and questionnaires. Results: The intervention resulted in a marked increase in knowledge scores (from 62.4 to 84.7). Appropriate feeding practices improved from 46% to 78%, while attendance at posyandu services increased from 58% to 85%. Early improvements in child growth indicators were observed, with 64% of children showing better weight-related outcomes. Conclusion: Strengthening primary health care capacity and community engagement effectively supports the implementation of stunting prevention policies. This approach demonstrates potential as a scalable model for accelerating stunting reduction in similar settings.